FAKTOR PENDUKUNG DAN PENGHAMBAT SINGLE PARENT DALAM MEMOTIVASI BELAJAR MAHASISWA (STUDI KASUS ORANGTUA MAHASISWA UNTAN) - Wahyudi, Heru; Asriati, Nuraini; Warneri, Warneri (STKIP Persada Khatulistiwa Sintang, 2024)
Single parents face numerous challenges in ensuring their children stay in school, besides managing household responsibilities and ensuring their children feel accepted in their surroundings. They also need to provide financial support for their children's education. This research aims to explore the supportive and inhibiting factors for single parents in motivating their children's learning. The research methodology employed is a qualitative case study approach. Data were collected through observation, interviews, and documentation by the researcher, with data validity tested using data triangulation. The study was conducted in several locations, including Pontianak, Kubu Raya, Singkawang, and Sambas, involving 5 informants who are single parents of students in the Economics Education program at FKIP Untan. Data analysis consisted of three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that single parents motivate their children's learning by providing encouragement, love, attention, financial support, and important values. However, they also face obstacles such as financial issues and time constraints, underscoring the crucial role of single parents in motivating their college-going children.